2007
DOI: 10.1177/1476718x07076679
|View full text |Cite
|
Sign up to set email alerts
|

what children know and can do when they start school and how this varies between countries

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
2
12
1
Order By: Relevance
“…Test-retest reliability for the UK version of the PIPS-BLA ranged from .91 to .98 and predictive validity for reading and maths was .70 and .65, respectively (Tymms, 2002). Studies have shown the four scales to be internally reliable with Cronbach's alphas of 0.95, 0.93, 0.86 and 0.86 for Reading, Mathematics, Vocabulary and Phonological Awareness, respectively (Merrell & Tymms, 2007).…”
Section: Pips-blamentioning
confidence: 99%
“…Test-retest reliability for the UK version of the PIPS-BLA ranged from .91 to .98 and predictive validity for reading and maths was .70 and .65, respectively (Tymms, 2002). Studies have shown the four scales to be internally reliable with Cronbach's alphas of 0.95, 0.93, 0.86 and 0.86 for Reading, Mathematics, Vocabulary and Phonological Awareness, respectively (Merrell & Tymms, 2007).…”
Section: Pips-blamentioning
confidence: 99%
“…These measures are referred to as PA measures in most publications relating to PIPS, e.g. Merrell and Tymms (), but another paper by these and additional authors (Tymms et al . ) noted these measures as being ‘abbreviated to phonics’.…”
Section: Evaluating the Reliability And Validity Of The Aqprmentioning
confidence: 99%
“…So, while creativity, through the Creative Partnerships programme, was being offered as a public policy ‘solution’ to concerns about disaffection and unhappiness in school, and to a plateau in pupils’ performance in national and international league tables of test results, it was required to complement rather than unsettle the standards agendas (Buckingham and Jones 2001; Tymms 2004; Merrell and Tymms 2007). The juggling act required is evident in the discursive shifts and balances observable even in early public interviews with senior Creative Partnerships' staff.…”
Section: Terms Two and Three: Partnership Developmentmentioning
confidence: 99%